A preliminary assessment of low level arsenic exposure and diabetes mellitus in Cyprus - Paisi, Martha; Ettinger, Adrienne S.; Makris, Konstantinos C.; Christophi, Costas A. (My University, 2012)
Background: A preliminary study was undertaken in a community of Cyprus where low-level arsenic (As) concentrations were recently detected in the groundwater that was chronically used to satisfy potable needs of the community. The main objective of the study was to assess the degree of association between orally-ingested As and self-reported type-2 diabetes mellitus (DM) in 317 adult (>= 18 years old) volunteers. Methods: Cumulative lifetime As exposure (CLAEX) (mg As) was calculated using the median As concentrations in water, individual reported daily water consumption rates, and lifetime exposure duration. Logistic regression models were used to model the probability of self-reported DM and calculate odds ratios (OR) in univariate and multivariate models. Results: Significantly higher (p < 0.02) CLAEX values were reported for the diabetics (median = 999 mg As) versus non-diabetics (median = 573 mg As), suggesting that As exposure could perhaps be related to the prevalence of DM in the study area, which was 6.6%. The OR for DM, comparing participants in the 80th versus the 20th percentiles of low-level As CLAEX index values, was 5.0 (1.03, 24.17), but after adjusting for age, sex, smoking, education, and fish consumption, the As exposure effect on DM was not significant. Conclusions: Further research is needed to improve As exposure assessment for the entire Cypriot population while assessing the exact relationship between low-level As exposure and DM.
Keywords: vascular-diseases; drinking-water; skin-lesions; cancer risk; bangladesh; prevalence